"Current dementia care: what are the difficulties and how can we advance care globally?" - Clarissa Giebel (BMC, 2020)
Abstract Background Dementia is a growing global public health concern, with post-diagnostic care often very limited. Depending on where people live, both within a country and depending on high-, middle-, and low-income countries, they might also face barriers in accessing the right care at the right time. Therefore, it is important to highlight recent evidence on the facilitators and barriers to dementia care, but also evidence on how to move dementia care forward. Main text Current dementia care is subject to several inequalities, including living in rural regions and being from a minority ethnic background. Evidence in this collection highlights the issues that both people living with dementia and unpaid carers are facing in accessing the right care, with evidence from Australia, Canada, Uganda, to the Netherlands, and further afield. Providing improved dementia-specific training to health care professionals and supporting medication and reablement interventions have been identified as possible ways to improve dementia care for all. Conclusions This special issue focuses on recent evidence on inequalities in dementia care across the globe and how dementia care can be advanced in various areas.